Persepsi Guru Penggerak Terhadap Peningkatan Mutu Pendidikan - Sherly, Rizki Meiliza (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to explore the perceptions of the driving teachers towards the program and initiatives to improve the quality of education at Elementary School 21 Palembang. The focus of this study is to understand how the driving teachers assess the effectiveness of the program that has been implemented and its impact on the quality of learning. The study used a qualitative approach with a case study method, involving in-depth interviews and observations as data collection techniques. The research participants consisted of driving teachers at the school. The results showed that driving teachers had a positive view of the quality improvement program, especially in terms of improving teaching skills and collaboration between teachers. However, there are challenges such as limited facilities and adequate policy support. The novelty of this study lies in the in-depth analysis of the role of driving teachers in elementary schools in the context of improving the quality of education in Palembang. The contribution of this study is expected to provide input for schools and policy makers in designing more effective quality improvement programs that are in accordance with teacher needs and school conditions.